A conceptual review on pretreatment anxiety management in a dental setting using hypnosis and progressive muscle relaxation - Puja Sabherwal; Namita Kalra; Rishi Tyagi; Amit Khatri; Shruti Srivastava (Archives of Depression and Anxiety - Peertechz Publications, 2022)
Dental anxiety is associated with the thought or idea of seeing the dentist and undergoing dental procedures. Anxiety-associated problems in the dental setting include avoidance of appointments, inability to provide successful dental care, and delay in optimal recovery. Anxiolysis is important to the level of being mandatory for suitable administration of dental care. Since times immemorial, dentists have struggled to manage anxiety successfully by employing changing concepts and strategies over time. Pharmacological modalities to allay anxiety-like sedation and general anesthesia are popular yet associated with an added cost per patient, side effects, expensive armamentarium, documentation, and patient monitoring. Non-pharmacological modalities for anxiety management have been employed over time but have limited nature of success. The use of hypnosis as a therapeutic modality for healing and resolving anxiety is known for over five thousand years and has been a part of many cultures over time. Progressive Muscle Relaxation, which was documented first in 1908 is based on the principle of releasing neuromuscular tension in the body which creates a state of emotional equilibrium. In the present paper, an in-depth review of the techniques i.e. Hypnosis and Progressive Muscle Relaxation is provided from the perspective of a dental clinician from historical evolution to practical recommendations. Both Hypnosis and Progressive Muscle Relaxation hold promise to be adjunct tools in the modern dentist's armamentarium to manage anxiety.